2022
DOI: 10.18502/ijm.v14i4.10230
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic groups, serogroups and virulence factors of uropathogenic Escherichia coli isolated from patients with urinary tract infection in Baghdad, Iraq

Abstract: Background and Objectives: Uropathogenic Escherichia coli (UPEC) is divided into different phylogenetic groups that differ in their antibiotic resistance patterns, serogroups and pathogenicity. This study aimed to investigate the prevalence of phylogenetic groups of UPEC isolates and their relationship with serogroups and virulence factors in patients with UTIs. Materials and Methods: Of the 412 urine samples tested a total of 150 UPEC were isolated and confirmed with PCR using 16S rRNA gene. Antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Certain virulence genes have been positively associated with large, transmissible plasmids encoding multidrug resistance (MDR) in ExPEC, high prevalence of the fyuA and ituA genes was observed in our study in the strains producing MDR/ESBLs. These results coincide with several investigations, which reported that UPEC fitness is not affected by genomic diversity, presence of virulence factors and production of ESBL, on the contrary, these genetic characteristics are an advantage for the dissemination of some clones of epidemiological importance ( 41 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…Certain virulence genes have been positively associated with large, transmissible plasmids encoding multidrug resistance (MDR) in ExPEC, high prevalence of the fyuA and ituA genes was observed in our study in the strains producing MDR/ESBLs. These results coincide with several investigations, which reported that UPEC fitness is not affected by genomic diversity, presence of virulence factors and production of ESBL, on the contrary, these genetic characteristics are an advantage for the dissemination of some clones of epidemiological importance ( 41 43 ).…”
Section: Discussionsupporting
confidence: 91%
“…The most common type of β-lactamase produced by UPEC is CTX-M-type extended-spectrum β-lactamase (ESBL), which hydrolyses third generation cephalosporins and monobactams as well as other β-lactams [ 166 ]. A recent study by Mohammed et al (2022) found that ESBL production was positively associated with certain serotypes, namely O8, O15, O21, O22, and O25 while being negatively associated with serogroups O1, O4, O7, and O16 [ 53 ]. Additionally, ampicillin resistance has been found to be significantly higher among serogroups O15 and O22 [ 10 ].…”
Section: Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…The O antigen is particularly variable, and currently there are 186 recognized O serotypes of E. coli [ 49 ]. Among these, the majority of UPEC belong to serogroups O1, O2, O4, O6, O7, O8, O14, O15, O16, O18, O21, O22, O25, O75, and O83 [ 50 , 51 , 52 , 53 , 54 ]. Among these O25, O15, and O8 are more frequently detected, although specific distribution is subject to geographical location and patient population [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In epidemiological studies, knowledge of the O-serogroups can help identify pathogenic lineages, classify E. coli for epidemiological studies, and identify outbreaks of diseases ( 32 ). Importantly, the relationship between antibiotic resistance and serogroups and virulence factors of E. coli was discovered in different disease conditions, such as children with septicemia ( 33 ), patients with urinary tract infection ( 34 ), and hospitalized patients ( 35 ). Nevertheless, similar studies on calf diarrhea are relatively limited.…”
Section: Introductionmentioning
confidence: 99%